Java Bytecode Compilation - *, Punit (IJRDO -Journal of Computer Science Engineering, 2015)
High-level languages used for programming like Java,C,C++ etc. Compiles a program to its equelent low level code which can be understood and executed by the machine. Here we will discuss about the Java compilation process, i:e, how Java compiles a code and what stages it have in compilation process. We basically focus on the Java bytecode and its advantages over native code. As we know the purpose of compilation is mainly to produce the executable version of a program. We also discuss the various approaches of compilation in java. The first approach is to compiling tha java bytecode, second is the two stages process going through the java bytecode to java native code, the third approach is to go through bypassing the java bytecode and going directly to natice machine code.